RNA Sequencing of the Pituitary Gland and Association Analyses Reveal PRKG2 as a Candidate Gene for Growth and Carcass Traits in Chinese Ningdu Yellow Chickens - Xiong, Xinwei; Zhou, Min; Zhu, Xuenong; Tan, Yuwen; Wang, Zhangfeng; Gong, Jishang; Xu, Jiguo; Wen, Yafang; Liu, Jianxiang; Tu, Xutang; Rao, Yousheng (Frontiers in Veterinary Science, 2022)
Growth and carcass traits are of great economic importance to the chicken industry. Candidate genes and mutations underlying growth and carcass traits can be utilized for marker-assisted selection to facilitate the improvement of chicken growth, thus highlighting the necessity for their identification. In this study, a total of 17 traits related to growth and carcass were measured in 399 Chinese Ningdu yellow chickens. RNA sequencing (RNA-seq) was performed to detect candidate genes using 12 pituitary gland samples (six per group), which exhibited extreme growth and carcass phenotypes: either a high live weight and carcass weight (H group) or a low live weight and carcass weight (L group). A differential expression analysis, utilizing RNA-seq, between the H group and the L group identified 428 differentially expressed genes (DEGs), including 110 genes up-regulated and 318 genes down-regulated. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of the identified genes showed a significant enrichment of 158 GO terms and two KEGG pathways, including response to stimulus and neuroactive ligand-receptor interaction, respectively. Furthermore, RNA-seq data, qRT–PCR, and quantitative trait transcript (QTT) analysis results suggest that the PRKG2 gene is an important candidate gene for growth and carcass traits of Chinese Ningdu yellow chickens. More specifically, association analyses of a single nucleotide polymorphism (SNP) in PRKG2 and growth and carcass traits showed that the SNP rs16400745 was significantly associated with 12 growth and carcass traits (P < 0.05), such as carcass weight (P = 9.68E-06), eviscerated weight (P = 3.04E-05), and semi-eviscerated weight (P = 2.14E-04). Collectively, these results provide novel insights into the genetic basis of growth in Chinese Ningdu yellow chickens. Additionally, the significance of the SNP rs16400745 could be incorporated into the selection programs involving this breed.